ZOOMORPHIC AND ANTHROPOMORPHIC PATRON CHARACTERS IN MAGIC FAIRY TALES - Jamila Askarova Bakhodirovna (International Journal of Literature and Language Studies, 2026)
The article explores the mythological characters who patronize the main character—the young man—in Uzbek folk magic fairy tales, examining their distinct types and classifications.